Non-hazardous and hazardous waste in Slovenia (Journal of Universal Excellence, 2026)
Research Question (RQ): "What types of waste from the classification list prevail the most in Slovenia?"Purpose: The purpose and goal of the research is to research, identify, study and compare types of waste from the classification list between 2002 and 2021 in Slovenia.Method: The research used a quantitative method. The data was obtained from the Statistical Office of the Republic of Slovenia, where we analysed them with the help of data processing tools such as Ecxel and Power BI Deskop.Results: The results of the survey show interesting information about the type and quantity of waste in Slovenia.   As can be seen from the research, the amount of waste has been increasing tremendously in recent years. At the same time, the share of hazardous waste is increasing. The results are given in tons units. It is evident that the export of waste is growing. The differences between deposited quantities according to the classification list prevail. Relevant legislative requirements must be observed at all stages. The survey was based on publicly available data.Organisation: The results of the survey show interesting information about the type and quantity of waste in Slovenia.   As can be seen from the research, the amount of waste has been increasing tremendously in recent years. At the same time, the share of hazardous waste is increasing. The results are given in tons units. It is evident that the export of waste is growing. The differences between deposited quantities according to the classification list prevail. Relevant legislative requirements must be observed at all stages. The survey was based on publicly available data.Society: The social dimension of waste demonstrates the need for  proper separation and appropriate disposal of all types. In the field of collection and storage, legal regulations have made progress in recent years and contributed to adequate protection of the environmentOriginality: The research was carried out within the course Management Information Systems of the master's study programme Quality Management at the Faculty of Organizational Studies in Novo mesto.Limitations/Future Research: For a broader view, in addition to waste from the classification list, it would be worthwhile to study in detail and obtain data for other types of waste. Organisations engaged in this activity should also be involved.
Keywords: waste; hazardous; non-hazardous; classification list; PivotTable; Excel; Power BI Deskop; quantity